2021
DOI: 10.1007/s40617-021-00610-7
|View full text |Cite
|
Sign up to set email alerts
|

Program Characteristics and Certification Examination Pass Rates: A Statistical Analysis of BACB-Published 2015–2019 Data

Abstract: The Behavior Analyst Certification Board (BACB) annually publishes data on the pass rates of institutions with verified course sequences (VCS). The current study analyzed BACB-published data from the years 2015-2019 and explored relations among program mode, number of first-time candidates, and examination pass rates. In a correlation analysis of number of first-time candidates and pass rates, there was a weak negative correlation, indicating that larger numbers of first-time candidates are associated with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Guinness and Turner (2022) found a weak, negative correlation between number of first-time candidates and pass rate for data aggregated across the years 2015–2019; that is, as the number of first-time candidates increased, the mean pass rate decreased. The current study found similar statistically significant correlations between first-time candidates and mean pass rate for only the years 2016, 2020, and 2021, but not for the remaining years.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Guinness and Turner (2022) found a weak, negative correlation between number of first-time candidates and pass rate for data aggregated across the years 2015–2019; that is, as the number of first-time candidates increased, the mean pass rate decreased. The current study found similar statistically significant correlations between first-time candidates and mean pass rate for only the years 2016, 2020, and 2021, but not for the remaining years.…”
Section: Discussionmentioning
confidence: 94%
“…One notable finding included a regression model revealing that providing coursework on campus predicted an increase of 11.06% points on a program's pass rate. Guinness and Turner (2022) examined the 2015-2019 BACB pass rate data and relations among different graduate program characteristics. Using a Spearman's rank correlation coefficient analysis, Guinness and Turner focused on the number of first-time test-takers from a graduate program and that program's pass rate and found a statistically significant, weak negative correlation.…”
mentioning
confidence: 99%
See 2 more Smart Citations